A high ratio of G1 to G0 phase cells and an accumulation of G1 phase cells before S phase progression after injurious stimuli in the proximal tubule - Iwakura, Takamasa (Physiol Rep, 2014)
Proximal tubule (PT) cells can proliferate explosively after injurious stimuli. To investigate this proliferative capacity, we examined cell cycle status and the expression of cyclin‐dependent kinase inhibitor p27, a G1 phase mediator, in PT cells after a proliferative or injurious stimulus. Rats were treated with lead acetate (proliferative stimulus) or uranyl acetate (UA; injurious stimulus). Isolated tubular cells were separated into PT and distal tubule (DT) cells by density‐gradient centrifugation. Cell cycle status was analyzed with flow cytometry by using the Hoechst 33342/pyronin Y method. Most PT and DT cells from control rats were in G0/G1 phase, with a higher percentage of PT cells than DT cells in G1 phase. Lead acetate and UA administration promoted the G0‐G1 transition and the accumulation of G1 phase cells before S phase progression. In PT cells from rats treated with lead acetate or a subnephrotoxic dose of UA, p27 levels increased or did not change, possibly reflecting G1 arrest. In contrast, p27 became undetectable before the appearance of apoptotic cells in rats treated with a nephrotoxic dose of UA. The decrease in p27 might facilitate rapid cell cycling. The decreased number of p27‐positive cells was associated with PT cell proliferation in renal tissues after a proliferative or injurious stimulus. The findings suggest that a high ratio of G1 to G0 phase cells and a rapid accumulation of G1 phase cells before S phase progression in the PT is a biological strategy for safe, timely, and explosive cell proliferation in response to injurious stimuli.